Lacking a backbone: The controversy over the 'National broadband network' and cyber-education projects - Raul V. Fabella; Emmanuel S. de Dios (University of the Philippines, School of Economics (UPSE), 2007)
The National Broadband Network (NBN) project and the Cyber Education Project (CEP) are state-initiated programs originally conceived to provide last-mile connectivity and interoperability to all government offices and all public schools, respectively. The backbone service required for this was to be procured from the private sector either from extant backbones or via BOT. When the soft loans from China became available, these two programs became scaled up to include two government-owned backbones. We examine the possible economic rationales for a government backbone and found the scaled-up NBN and CEP severely wanting. The prior question we address is: Does the Philippines need a government-owned backbone? Our answer is: No.
Keywords: 330; Subvention; Breitbandkommunikation; Kritik; Philippinen